Mempraktikkan Hukum Kasih di Era Pandemi Covid-19 - Nehemia Pasaribu (PNEUMATIKOS: Jurnal Teologi Kependetaan, 2022)
Abstract: Covid-19 is a weakness experienced by everyone, which has an impact on health, poverty, and even society. During the COVID-19 pandemic, government regulations regarding health protocols were enforced, so that in carrying out activities there were social restrictions to reduce the spread of the virus, social restrictions also had an impact on church activities. But the church must still express the love that Jesus taught in the second commandment, which states "love your neighbor". This article aims to provide an understanding of how to practice the law of love. The method in this study uses an analytical literature approach. In this finding, it was found that during the Covid-19 pandemic, the church must continue to practice the law of love without violating the provisions of government regulations regarding health protocols.Abstrak: Covid-19 adalah sebuah kelemahan yang di alami semua orang, yang berdampak pada kesehatan, kemiskinan, bahkan sosia. Di masa pandemi Covid-19 diberlakukan peraturan pemerintah tentang protokol kesehatan, sehingga dalam melakukan kegiatan ada batasan sosial untuk mengurangi penyebaran virus, pembatasan sosial juga berdampak dalam kegiatan gereja. Namun gereja harus tetap menyatakan kasih yang telah diajarkan Yesus di dalam hukum yang kedua, yang menyatakan “kasihilah sesamamu manusia”. Artikel ini mempunyai tujuan untuk memberikan pemahaman tentang bagaimana cara mempraktekkan hukum kasih. Metode dalam penelitian ini menggunakan pendekatan literatur analisis. Dalam temuan ini diperoleh bahwapada masa pandemi Covid-19, gereja harus tetap memraktekkan hukum kasih tanpa melanggar ketetapan peraturan pemerintah tentang protokol kesehatan.